Agile Governance in Optimizing Digital Literacy for Micro, Small and Medium Enterprises (MSMe) in Kulon Progo Regency - Atmojo, Muhammad Eko; Darumurti, Awang; Hanif, Nita Aribah (Universitas Muhammadiyah Malang, 2024)
The COVID-19 pandemic has had an impact on all sectors, especially the economy in Indonesia and the regions, one of which includes Micro, Small and Medium Enterprises (MSMEs). Data from the DIY Cooperatives and UMKM Service shows that 59% of MSMEs have experienced the direct impact of the COVID-19 pandemic, on the other hand MSMEs have a very strategic role in improving the Indonesian economy. Kulon Progo Regency is one of the districts that has a solution to overcome the problem of marketing MSME products, one of which is belabeliku.com. Having this solution does not mean there are no problems, because there are many MSMEs in Kulon Progo Regency who do not understand digital literacy well. The method used in this study is a qualitative method, one of the techniques is interviews and documentation, besides that this research also utilizes the artificial intelligent Nvivo 12 plus as an analytical tool. Based on the results of the research, it can be concluded that the government has made a special policy by providing training for MSME actors, collaborating with the Yogyakarta Regional Development Bank (BPD) in providing electronic payment services, and creating a marketplace platform. With the policies that have been made, it will be very helpful for MSME actors, especially the platform creation policy in marketing MSME products. However, the platform created is not adequate and optimal, besides that the platform created is still unable to compete with other marketplace applications.